Hypoxia-related gene expression profile in childhood acute lymphoblastic leukemia: prognostic implications. Issue 8 (August 2014) - Silveira, Vanessa S.; Freire, Bruno M. R.; Borges, Kleiton S.; Andrade, Augusto F.; Cruzeiro, Gustavo A. V.; Sabino, João Paulo J.; Glass, Mogens Lesner; Yunes, José Andres; Brandalise, Silvia Regina; Tone, Luiz Gonzaga; Scrideli, Carlos Alberto
Abstract A cellular hypoxic condition is a key event in several human cancers, but knowledge about its role in childhood acute lymphoblastic leukemia (ALL) is very limited. In the present study, the gene expression profile of hypoxia-related genes (HIF1A, CA9, VEGF and SCL2A1) was evaluated in bone marrow samples of 113 pediatric patients. HIF1A mRNA up-regulation was significantly associated with higher 5-year event-free survival rates in patients with B-ALL as well as in the overall ALL population in both univariate and multivariate analysis (p = 0.023 and p = 0.041, respectively). In gene expression analysis, low oxygen levels promoted HIF1A activation in a time-dependent manner, in both ALL cell lines. In vitro cytotoxic assays suggested an initial trend toward hypoxia-related resistance in the first 24 h, but evaluation at later time points (48–72 h) clearly showed that there was no relevant difference in drug response when comparing hypoxic and normal oxygen level conditions. Modulation of mRNA expression of several hypoxia-related genes was also observed after hypoxic exposure in a cell specific manner, suggesting that HIF1A mRNA expression could play a different role in specific subtypes of leukemia. Despite the remaining questions regarding hypoxia-mediated mechanisms, these findings could be helpful to provide new insights into the role of hypoxia in childhood ALL.